2019
DOI: 10.1002/jclp.22851
|View full text |Cite
|
Sign up to set email alerts
|

Path analytic modeling of psychologists’ openness to performing clinical work with telepsychology: A national study

Abstract: Objective: To examine whether the Theory of Reasoned Action (TRA) and Technology Acceptance Model (TAM) apply to psychologists' openness to using telepsychology. Method: Participants were 1,791 psychologists currently practicing psychotherapy. Participants represented all 50 US states and averaged 26.33 (SD = 11.18) years in clinical practice. The study used a cross-sectional, national online design. Results: Path analyses derived from the TRA and TAM evidenced poor fit. A newly-developed, third model achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 42 publications
6
44
0
Order By: Relevance
“…More than any other theme, the articles in this special issue underscore the critical nature of strong telepsychology training as a growth opportunity for the field. Pierce, Perrin, and McDonald (2020) found in their path model that the strongest predictors of psychologists' use of telepsychology were subjective norms, perceived ease of use, and perceived usefulness of telepsychology. Put simply, psychologists who do not use telepsychology do not feel that others are using it or that it is easy to use or useful.…”
Section: Telepsychology Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…More than any other theme, the articles in this special issue underscore the critical nature of strong telepsychology training as a growth opportunity for the field. Pierce, Perrin, and McDonald (2020) found in their path model that the strongest predictors of psychologists' use of telepsychology were subjective norms, perceived ease of use, and perceived usefulness of telepsychology. Put simply, psychologists who do not use telepsychology do not feel that others are using it or that it is easy to use or useful.…”
Section: Telepsychology Special Issuementioning
confidence: 99%
“…Some seemingly obvious exceptions to this general rule may apply for specific clinical services, such as neuropsychological assessment, although evidence is mounting that certain neuropsychological assessments can feasibly be administered through telepsychology (Galusha‐Glasscock, Horton, Weiner, & Cullum, 2016). Telepsychology trainings and readings have to spend substantial time countering preconceived biases and educating psychologists and trainees that telepsychology works and how it can extend in‐person services (Pierce et al, 2020). Theory‐driven intervention research in this area would identify what barriers are present for psychologists (e.g., Perry et al, 2020), as well as exactly what types of information and experiences effectively help psychologists with strong biases against telepsychology overcome them.…”
Section: Telepsychology Special Issuementioning
confidence: 99%
“…General skepticism toward telepsychotherapy is also present and is particularly strong among practitioners. In a sample of 1,791 US psychotherapists, nearly 80% reported that they did not use telepsychotherapy within their own practice (Pierce et al, 2019). Overall, learning curves in the adoption of new e-mental health technologies by both patients and psychologists have progressed far more slowly than initially expected, thus tallying with the estimate that it takes, on average, 16 years for a healthcare innovation to be implemented (Rogers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although closely related, the term “telepsychology” is not used here since it also includes other types of psychology services delivered via technology besides psychotherapy and counseling (e.g., assessment or psychoeducation) and is limited to psychologists while psychotherapy might be delivered by other professionals. For more information on practitioners' attitudes toward telepsychology, see for example, Pierce, Perrin, and McDonald (2019). …”
mentioning
confidence: 99%